2004
DOI: 10.2202/1469-3569.1070
|View full text |Cite
|
Sign up to set email alerts
|

Market and Nonmarket Barriers to Internet Wine Sales: The Case of Virginia

Abstract: We discuss the political and legal environment surrounding Internet wine sales, and consider the arguments in the debate over direct shipment bans on wine by investigating the wine market in the Northern Virginia suburbs of Washington, DC. Using a sample of wines identified by Wine and Spirits magazine's annual restaurant poll, we find that 15 percent of wines available online were not available from retail wine stores within 10 miles of McLean, Virginia during the month the data were collected. Our results al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In addition, Gokcekus and Nottebaum (2012) find that states with little tax revenue, proxied by the fraction of federal aid received, tend to prohibit direct wine shipments. Wiseman and Ellig (2004) investigated wine prices in Virginia and concluded that the prohibition of out-of-state online sales has resulted in a 10% increase in prices. When the state of Virginia legalized direct wine shipping to consumers from out-ofstate sellers in 2003, not only the price level but also the retail price variance among retail outlets decreased dramatically (Wiseman and Ellig, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gokcekus and Nottebaum (2012) find that states with little tax revenue, proxied by the fraction of federal aid received, tend to prohibit direct wine shipments. Wiseman and Ellig (2004) investigated wine prices in Virginia and concluded that the prohibition of out-of-state online sales has resulted in a 10% increase in prices. When the state of Virginia legalized direct wine shipping to consumers from out-ofstate sellers in 2003, not only the price level but also the retail price variance among retail outlets decreased dramatically (Wiseman and Ellig, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Putting aside these contributions to the literature on alcohol regulation, our work builds most directly on a series of papers by Wiseman and Ellig (, ) that analyzed the impacts of bans on (and subsequent legalization of) direct wine shipment. More specifically, Wiseman and Ellig () found that when interstate direct shipment was illegal in Virginia, online prices of premium wines were lower than prices in northern Virginia bricks‐and‐mortar stores, and online variety was greater. A follow‐up study found that repeal of Virginia's ban on interstate direct wine shipment corresponded to the reduction in the average online‐offline price differential by 40 percent (Wiseman & Ellig ).…”
Section: Analyzing Alcohol Regulation: the Devil Is In The Details Nmentioning
confidence: 99%
“…The current study builds directly on these works to assess the impacts of the types of laws that have been passed in the wake of Granholm v. Heald by revisiting the analysis in Wiseman and Ellig (, ) to analyze how (if at all) their results, in regard to price effects, would change if the State of Virginia had adopted some of the laws that are currently found in other states today: laws that might permit some direct interstate wine shipment but limit the entities that can ship. Perhaps it is the case that only allowing direct shipment by wineries, or wines produced by smaller wineries, provides most of the potential consumer benefits, and the remaining restrictions are primarily nuisances.…”
Section: Analyzing Alcohol Regulation: the Devil Is In The Details Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The changing nature of the states' three-tier systems and related regulatory issues is a topic that deserves to be closely followed by industrial organization economists. 15 These cases involve two constitutional issues (Wiseman and Ellig, 2004). First, the "dormant" Commerce Clause prohibits economic protectionism that favors in-state interests and thus limits how that states can regulate alcohol under the Twenty-First Amendment.…”
Section: Shipments Of Beer and Winementioning
confidence: 99%